1988
DOI: 10.1136/bmj.296.6627.968
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins in breast milk, neonatal cord blood, and serum of pregnant women

Abstract: Aflatoxins in breast milk, neonatal cord blood, and serum of pregnant women Aflatoxins are fungal metabolites commonly found as toxic contaminants of food commodities in the tropics.' Aflatoxins have been detected in breast milk from mothers in the Sudan.2 A study in the United States has shown that aflatoxins cross the complex porcine placenta and exert adverse biological effects on neonatal pigs.3 Investigations conducted in Accra, Ghana, and Jos, Nigeria, therefore, sought to confirm the presence of aflatox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 2 publications
1
34
1
Order By: Relevance
“…Other studies show associations between aflatoxins and stillbirths (Lamplugh et al 1988;Vries et al 1989), liver cirrhosis (Kuniholm et al 2008), jaundice in newborns (Abdulrazzaq et al 2004;Abulu et al 1998;Ahmed et al 1995;Sodeinde et al 1995) and immunosuppression (Jiang et al 2005;Turner et al 2003).…”
Section: Cgiar Agricultural Research On Food Safety and Aflatoxinsmentioning
confidence: 94%
“…Other studies show associations between aflatoxins and stillbirths (Lamplugh et al 1988;Vries et al 1989), liver cirrhosis (Kuniholm et al 2008), jaundice in newborns (Abdulrazzaq et al 2004;Abulu et al 1998;Ahmed et al 1995;Sodeinde et al 1995) and immunosuppression (Jiang et al 2005;Turner et al 2003).…”
Section: Cgiar Agricultural Research On Food Safety and Aflatoxinsmentioning
confidence: 94%
“…Even the unborn are exposed to aflatoxins and its associated burdens. Women may expose their unborn child to aflatoxins during pregnancy and through breastfeeding, if they consume aflatoxin contaminated foods (Gong et al, 2003;Lamplugh et al, 1988;Oluwafemi and Ibeh, 2011). Food insecurity frequently forces people to consume contaminated foods because no other food options are available.…”
Section: Aflatoxins In Africamentioning
confidence: 99%
“…Infection with hepatitis B virus is almost universal during childhood in West Africa, and Lung (mj Skin (172-1731 Breast Cervix uteri (180) Prostate (185) Bladder (188) Eye (1 90) Lymphomas (200)(201)(202) Leukaemias (204)(205)(206)(207)(208) All sites a high proportion of the adult population are chronic carriers of HBsAg (Barin et al, 1981;Whittle et al, 1983). Aflatoxin is also probably important in the aetiology of hepatocellular carcinoma (IARC, 1987) and studies elsewhere in West Africa have suggested considerable population exposure (Lamplugh et al, 1988;Wild et al, 1990). The incidence of stomach cancer is moderately high by world standards, similar to the incidence seen in US blacks (Muir et al, 1987), and the highest so far recorded in Africa.…”
Section: Discussionmentioning
confidence: 97%